Design, Validation, and Clinical Implementation of a Gap-Polymerase Chain Reaction Method for α-Thalassemia Genotyping Using Capillary Electrophoresis. (4th March 2017) - Basha, Basma; Mularo, Frank; Cook, James R.
Abstract: α-Thalassemia (α-thal) is genetically heterogeneous with most cases caused by variably sized deletions of the HBA1 and/or HBA2 loci. In this report, we describe the development, validation, and implementation of a novel gap-polymerase chain reaction (gap-PCR)/capillary electrophoresis (CE). method. This assay utilizes two multiplex reactions and CE to detect the following deletions: –α 3.7 (rightward), –α 4.2 (leftward), –(α) 20.5, – – SEA (Southeast Asian), – – MED, – – FIL and – – THAI . Validation studies using 36 previously characterized patient samples and plasmid controls demonstrated 100.0% accuracy. Following clinical implementation, 423 patients were analyzed over 24 months. Two hundred and twenty-seven cases (46.0%) showed abnormal results including heterozygous –α 3.7 ( n  = 114, 27.0%), homozygous –α 3.7 ( n  = 96, 23.0%), heterozygous – – SEA ( n  = 9, 2.0%), heterozygous –α 4.2 ( n  = 5, 1.0%), heterozygous – – MED ( n  = 1, <1.0%), and compound heterozygous –α 3.7 /–α 4.2 ( n  = 2, <1.0%) deletions. Correlation with red blood cell (RBC) parameters showed that patients with a deletion of two or more genes were associated with significantly lower mean corpuscular volume (MCV) and mean corpuscular hemoglobin (Hb) (MCH) levels than patients with wild-type results. This novel multiplex gap-PCR protocol reliably detects the seven most common deletions giving rise to α-thal. Use of the fluorescently labeled CE method provides for a high throughput workflow suitable to a clinical diagnostic laboratory serving a multiethnic population.